Uji Karakteristik Hipotesis Bangunan Rumah Tinggal yang Memanfaatkan Pendinginan Evaporasi dengan Computational Fluids Dynamics (CFD) - Nanda, Riski Yoga, Ir. H. Sarjito, MT., Ph.D (2016)
Air conditioning in housing is required to obtain thermal comfort zone, especially at urban areas that have problems with the limitations of land. One of alternative room air conditioning (AC) that environmently-friendly to reduce refrigeration system is evaporative cooling system. The aim of the research is to investigate characteristic of air conditioning inside the house wich utilize evaporative cooling system using Computational fluids dynamics (CFD ). The research was done by describing 3 different times which are 09.00-10.00 (in the morning), 12.00-13.00 (at noon) and 19.00-20.00 (at night) with incoming air in different properties. The air characteristic test was done by measuring velocity of the wind, relative humidity (RH) and temperatures at 28 positions of measurement cup (PU), where PU were spreaded at 3 places, (1) in front of the house; (2) at the interior; and (3) at the exterior. The measurement was conducted by making square plane of 2x2m with high of 1.5 m above floor of 28 PU. CFD simulation results showed that the cooling effect evaporative felt on the 1st floor with the average temperature reduction of 1.5 oC from the ambient temperature and increase RH of 6.75 % from ambient RH. While the vertical ventilation work effectively in supporting air circulation. The movement of the wind can be felt throughout the house with the average velocity of 0,175 m/s. Key Words : Comfort zone, Evaporative cooling, CFD